2021
DOI: 10.1186/s13052-021-00976-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on the Emergency Department of a tertiary children’s hospital

Abstract: Background Italy was the first country in Europe affected by COVID-19: the emergency started on February 20, 2020, culminating with national lockdown on March 11, which terminated on May 4, 2020. We describe how the pandemic affected Emergency Department (ED) accesses in a tertiary children’s hospital, composed by two different pediatric centers, one located in Rome’s city center and the second, Palidoro (regional COVID-19 center), in its surrounding metropolitan area, both in the Lazio region,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
61
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 36 publications
12
61
2
3
Order By: Relevance
“…The median waiting time in the PED was found to have decreased by threefold and twofold for 50% and 75% of patients, respectively. Significant decreases in the number of emergency room admissions have also been reported in other studies [ 12 , 13 ]. Reducing waiting time is often an important goal in PED reorganization and a significant metric that is monitored by health authorities [14] .…”
Section: Discussionsupporting
confidence: 78%
“…The median waiting time in the PED was found to have decreased by threefold and twofold for 50% and 75% of patients, respectively. Significant decreases in the number of emergency room admissions have also been reported in other studies [ 12 , 13 ]. Reducing waiting time is often an important goal in PED reorganization and a significant metric that is monitored by health authorities [14] .…”
Section: Discussionsupporting
confidence: 78%
“…Gender and age were almost equally distributed between the 2 years. ED visits consistently dropped in March (− 52%) and April (− 52%) 2020 during the first pandemic wave as already described in other Italian settings [6][7][8]. During summer, the reduction of SARS-CoV-2 contagion and COVID-19 related-hospitalization rates were associated with a gradual increase in ED presentations.…”
supporting
confidence: 64%
“…During the COVID-19 pandemic, a consistent decrease in ED visits has been recorded worldwide. Italy has been the first western country to register a reduction in individuals seeking medical attention in EDs, although studies describing this phenomenon are mostly limited to the first pandemic wave [6][7][8].…”
mentioning
confidence: 99%
“…Matera et al demonstrated that during the lockdown period, Emergency Room admissions decreased by 81% compared to 2019, and this reduction was significantly higher for air communicable diseases [5]. Raucci et al also demonstrated a strong reduction in visits in Emergency Department for Respiratory Diseases [6].…”
Section: Introductionmentioning
confidence: 99%